Evaluasi Pengelolaan Sampah di Kelurahan Baru Tengah - Rini, Intan Dwi Wahyu Setyo; Yani, Fitdri Handra; Hayati, Rina Noor (SPECTA Journal of Technology, 2023)
Kelurahan Baru Tengah, located in Balikpapan, is a densely populated area. Still, the lack of community participation and awareness in waste management is seen from the accumulation of waste outside the waste shelter (TPS). This condition has an impact on hygiene and public health. Waste accumulation outside the waste shelter can also be caused by inadequate TPS facilities or limited TPS capacity. Therefore, research was carried out to evaluate waste containers in Kelurahan Baru Tengah. This research was conducted through field observations and waste sampling per the procedures listed in the SNI. Waste sampling was conducted eight days at three residential locations based on house conditions and two waste shelter locations to determine waste generation, composition, and characteristics. The results of this study showed that waste generation for permanent housing was 0.13 kg/person/day, waste generation for semi-permanent housing was .0.13 kg/person/day, and for non-permanent housing was 0.21 kg/person/day. The waste composition in Kelurahan Baru Tengah was dominated by organic waste at 50%, consisting of food and vegetable and fruit waste. The characteristic test showed that the waste in Kelurahan Baru Tengah had a moisture content of 90% and a C/N ratio of 17.6%.